Outcome of Non-Closure of Buccal Mucosal Graft Harvest Site in Comparison to Primary Closure (Bangladesh Journal of Urology, 2020)
Objective: To compare prospectively the outcome of non-closure of buccal mucosal graft harvest site in comparison to its’ primary closure.Methods: Patients who underwent BMG harvest for urethroplasty were randomized into 2 groups; in group 1 donor site was closed and in group 2 it was left open. Pain at BMG harvest site was the primary variable. Postoperative resumption to regular diet and difficulty in mouth opening were 2 other variables. After buccal mucosal graft harvesting, donor area was either closed (group 1) or left open and allowed to heal by second intention. In the postoperative period, visual analog score was to evaluate pain at donor area. Self made questionnaires were used to assess limitation to mouth opening andthe time to resumption of liquid and solid diet.Results: Thirty two patients were studied, 16 in each group from December 2012 to June 2014. Mean age among the two groups were almost same(closure group, 42.37 years Vs 41.26 years in nonclosure group). Mean stricture length was 4.75 cm in closure group and 7.53 cm in non -closure group. In closure group, BMG was harvested from single cheek in most of the patients but in non closure group, graft was harvested from both cheeks and also from lower lips in few patients. Mean post operative pain score was 5.06 and 3.68 at day 1 in group 1 and group 2, respectively (P < 0.008) but as the days progressed, pain score in both groups became comparable. Return to oral intake in terms of liquid and solid diet was comparable between the groups. Difficulty with mouth opening was maximal during the first week with no difference among the two groups.Conclusion: Pain appears to be worse in the immediate post operative period with suturing of the harvest site. There is no difference in long term morbidity whether the graft site is closed or left open. It may be best to leave buccal mucosa harvest sites unsutured.Bangladesh Journal of Urology, Vol. 20, No. 1, January 2017 p.26-30